A public/private benefits framework for the design of polices oriented to sustainability in agriculture: An application to olive growing. (15th December 2016) - Carmona-Torres, Carmen; Parra-López, Carlos; Sayadi, Samir; Chirosa-Ríos, Manuel
Highlights: An integrated framework for policy design oriented to olive sustainability is proposed. Multiple functions of agriculture, stakeholders, and benefits/costs are considered. Soil management, fertilization, irrigation and pruning practices highly impact sustainability. Extension, agri-environment schemes and territorial contracts may improve sustainability. Sustainability is not incompatible with private benefits for olive growers.